Health Education Through The “Lawan TBC” Movement to Improve Tuberculosis Prevention Knowledge in Islamic Boarding Schools - Marinda Dwi Puspitarini; Kartuti Debora; Aldilia Wyasti Pratama; Yuriske Agnovianto; Diana Arum Lisnawati; Muhammad Hefdi; Clarissa Septianingrum (Communautaire: Journal of Community Service, 2026)
Tuberculosis (TB) remains a major public health concern in Islamic boarding schools due to the high risk of disease transmission in communal living environments. This study aimed to evaluate the effectiveness of the "Lawan TBC" educational movement in improving students' knowledge of tuberculosis prevention. A pre-experimental one-group pretest–posttest design was conducted among 38 students in grades 10–12 at an Islamic boarding school in Surabaya. The intervention included lectures, interactive discussions, and question-and-answer sessions on TB transmission, symptoms, prevention, and proper cough etiquette. Knowledge was assessed using questionnaires administered before and after the intervention. Data were analyzed using the Wilcoxon Signed-Rank Test. The mean pretest score was 35.53 ± 10.05, increasing to 46.32 ± 7.86 in the posttest, with a mean difference of 10.79 points. Statistical analysis showed a significant improvement in knowledge after the intervention (p = 9.45 × 10⁻⁸; p < 0.01). The findings demonstrate that the "Lawan TBC" educational movement effectively improves students' knowledge of tuberculosis prevention. Educational programs in Islamic boarding schools can support TB prevention efforts and promote preventive health behaviors among adolescents.